1995
DOI: 10.1161/01.cir.91.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cardiolipin Antibodies and Risk of Myocardial Infarction in a Prospective Cohort of Middle-Aged Men

Abstract: In a prospective cohort of healthy middle-aged men, the presence of a high aCL antibody level is an independent risk factor for myocardial infarction or cardiac death. Antibodies to cardiolipin and oxidized LDL may, at least in part, represent cross-reactive antibody populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
149
2
7

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 327 publications
(163 citation statements)
references
References 23 publications
5
149
2
7
Order By: Relevance
“…A number of studies have previously demonstrated that aPL can increase the risk of thrombotic events, suggesting an important role for these autoantibodies in the pathogenesis of APS (28,29). However, their role in the development of lupus has largely remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have previously demonstrated that aPL can increase the risk of thrombotic events, suggesting an important role for these autoantibodies in the pathogenesis of APS (28,29). However, their role in the development of lupus has largely remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus patients who develop aPL have an increased risk of developing thrombocytopenia (range 11-40%, versus ϳ4-17% in aPL-negative SLE), hemolytic anemia (range 5-16% versus 2-8%), and symptoms traditionally thought of as being associated with APS rather than SLE, such as arterial or venous thrombosis and recurrent fetal loss (6)(7)(8)(9)(10)(28)(29)(30)(31). In our study, thrombocytopenia and hemolytic anemia were found to be significantly more common among aPL-positive patients, as was the risk of thrombotic events usually associated with APS.…”
Section: Discussionmentioning
confidence: 99%
“…In stroke patients, 18% of young patients (mean age, 38 years) were positive for antiphospholipid antibodies (LA and aCL) and 9.7% of patients who developed stroke for the first time were positive for aCL according to the Antiphospholipid Antibodies in Stroke Study Group (APASS) [8,9]. In patients with myocardial infarction, the prevalence of aCL is reported to be between 5% and 15% [10]. In 543 blood donors under 65 years of age, 2% were positive for aCL [11].…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between the levels of anticardiolipin antibodies and antibodies to oxidized LDL was also found in a prospective study of healthy men in whom the presence of increased levels of both antibodies predicted myocardial infarction [12,13]. However, the effect was additive, suggesting that their biological functions, despite the cross-reaction, may differ in vivo [13].…”
Section: Introductionmentioning
confidence: 65%
“…However, the effect was additive, suggesting that their biological functions, despite the cross-reaction, may differ in vivo [13].…”
Section: Introductionmentioning
confidence: 99%